The UTILIZATION OF MEDICINAL PLANT COLLECTION IN BOGOR BOTANICAL GARDEN FOR WOUND HEALING - istiqomah, sakina; Roni, Asep; Kusriani, Raden Herni; Hidayat, Syamsul (Jurnal Kesehatan Farmasi, 2025)
Medicinal plants play an essential role in human health by treating various diseases, including wound healing. Bogor Botanical Gardens (KRB) serve as a conservation site for numerous medicinal plant species. This study aims to explore the use of medicinal plants in KRB for wound healing activities. Using a qualitative descriptive method, data were collected on plant species with known wound-healing properties. The study identified 65 species with potential, predominantly from the Fabaceae family. Notable examples include Archidendron clypearia, Caesalpinia coriaria, Cassia fistula, Peltophorum pterocarpum, Spatholobus littoralis, and Tamarindus indica, each with specific ethnobotanical uses. Among them, Tamarindus indica was found to be the most effective, capable of closing wounds by the fifth day. Plant parts used in treatment include leaves, bark, stems, sap, and others, commonly applied through compression or topical use. This study highlights the significant potential of KRB’s medicinal plant collection in contributing to traditional and scientific approaches to wound healing.